anonymous
  • anonymous
if f(x)=2x-3 and g(x)=2x^2+1 find A.f(g(2)) B. g(f(x)) C. does f(x) have and inverse if so find the inverse of f(x)
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
f surely has an inverse because it is a line and therefore one to one.
anonymous
  • anonymous
f says 'multiply by 2 then subtract 3' so f inverse would say to do the opposite things in the opposite order: add 3 and divide by 2 so \[f^{-1}(x)=\frac{x+3}{2}\]
anonymous
  • anonymous
if this is confusing, rewrite \[f(x)=2x-3\] as \[y = 2x-3\] then switch x and y (because that is what the inverse does) to get \[x=2y-3\] and solve this for x: \[x=2y-3\] \[x+3=2y\] \[\frac{x+3}{2}=y\] and y is your inverse.

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
is that the answer for C
anonymous
  • anonymous
yes. was it clear?
anonymous
  • anonymous
ok so whats the answers for a and b
anonymous
  • anonymous
\[f(g(x))=f(2x^2+1)=2(2x^2+1)-3\]
anonymous
  • anonymous
i guess there is a little algebra to do now: \[2(2x^2+1)-3=4x^2+2-3=4x^2-1\]
anonymous
  • anonymous
but it was f(g(2))
anonymous
  • anonymous
is it clear what i did? first write \[f(g(x))\] then replace \[g(x)\] by \[2x^2+1\] and then rewrite f replacing \[x\] by \[2x^2+1\]
anonymous
  • anonymous
oh well if it is \[f(g(2))\] then since \[f(g(x))=4x^2-1\] then \[f(g(2))=4(2^2)+1=17\]
anonymous
  • anonymous
typo sorry. \[4(2^2)-1=15\]
anonymous
  • anonymous
or you could say \[g(2)=2(2^2)+1=9\] and \[f(9)=2\times 9 - 1=15\]
anonymous
  • anonymous
ok
anonymous
  • anonymous
\[g(f(x))=g(2x-3)=2(2x-3)^2+1\]
anonymous
  • anonymous
this requires more algebra: \[2(2x-3)^2+1=2(2x-3)(2x-3)+1=2(4x^2-6x+9)+1\] \[=8x^2-12x+18+1=8x^2-12x+19\] if my algebra is correct.
anonymous
  • anonymous
ok for a how come its 4(2^2)-1
anonymous
  • anonymous
and not 2(2^2) +1

Looking for something else?

Not the answer you are looking for? Search for more explanations.